Nano-modification of Si-wafer surfaces using low-cost ambient air diffuse plasma - Homola, Tomáš; Prysiazhnyi, Vadym [UNESP]; Stupavská, Monika (Inderscience Publishers, 2015)
In this paper, we demonstrated the cleaning and nano-oxidation of Si-wafer surfaces by atmospheric pressure plasma, generated in ambient air using diffuse coplanar surface barrier discharge. Plasma treatment for one second resulted in a significant reduction of water contact angle. The increase in wettability was observed and explained by chemical changes on the analysed Si-wafer surfaces. These changes were analysed by X-ray photoelectron spectroscopy which showed a considerable decrease in the presence of carbon and a significant increase of oxygen on the analysed surfaces.
Keywords: DBD; Diffuse plasma; Nano-modification; Silicon wafer; Surface treatment